2021
DOI: 10.3389/fphar.2021.617555
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Pharmacological Mechanism of 2-Dodecyl-6-Methoxycyclohexa-2,5 -Diene-1,4-Dione Against Lung Cancer Based on Network Pharmacology and Experimental Evaluation

Abstract: Background: 2-Dodecyl-6-Methoxycyclohexa-2, 5-Diene-1,4-Dione (DMDD) was purified from the roots of Averrhoa carambola L. Previous research demonstrated that DMDD is a small molecular compound with significant therapeutic potential for tumors. However, the potential targets and pharmacological mechanism of DMDD to treat lung cancer has not been reported.Methods: We employed network pharmacology and experimental evaluation to reveal the pharmacological mechanism of DMDD against lung cancer. Potential therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…During article searching, two essays [ 14 , 15 ] regarding to lung adenocarcinoma (LAUD) and lung squamous cell carcinoma (LUSC) were from the same database as an included article [ 15 ] on lung cancer (LC). In order to prevent repeated inclusion of data, we have deleted the above two essays.…”
Section: Methodsmentioning
confidence: 99%
“…During article searching, two essays [ 14 , 15 ] regarding to lung adenocarcinoma (LAUD) and lung squamous cell carcinoma (LUSC) were from the same database as an included article [ 15 ] on lung cancer (LC). In order to prevent repeated inclusion of data, we have deleted the above two essays.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that DMDD exhibited anti-tumor effects against BC in mice (8)(9)(10)(11). In addition, DMDD can block tumorigenesis through modulation of the cell cycle in lung cancer (12). However, DMDD has poor solubility in water, thus limiting its application as an antitumor agent.…”
Section: Original Articlementioning
confidence: 99%
“…During article searching, two literatures [13,14] regarding to lung adenocarcinoma (LAUD) and lung squamous cell carcinoma (LUSC) were from the same database as an included article [14] on lung cancer (LC). In order to prevent repeated inclusion of data, we have deleted the above two literatures.…”
Section: Data Extraction and Checkingmentioning
confidence: 99%